Subaerial speleothems and deep karst in central Sweden linked to Hirnantian glaciations - Björn Kröger; Jan Ove R. Ebbestad; Oliver Lehnert; Clemens V. Ullmann; Christoph Korte; Robert Frei; Christian M. Ø. Rasmussen (2016)
The limestones of the upper Katian Boda mud mounds (Ordovician) of the Siljan district in central Sweden are deeply fractured. The fissures were partly synsedimentary and are often lined with stromatolite-like crusts. These crusts thus far are the only known subaerial Ordovician speleothems. They reach depths of up to 30 m below the former mound top. Macroscopically the crusts form decimetre-sized, cone-shaped domal aggregates, stalactites and stalagmites. Microfabric and morphology identify them as microbially mediated speleothems in a dark environment. Combined Sr and C isotope values indicate a formation of the speleothems from meteoric waters without influence of a significant soil horizon. For the first time the age of the speleothems can be precisely constrained by δ 13 C whole-rock and brachiopod shell isotope data to the mid-Hirnantian. Repeated and/or prolonged subaerial exposure of the Boda mud mounds during the Hirnantian is evident from karst surfaces and early cements in the mound capping carbonates. The speleothems and the karst surfaces record an estimated sea-level fall in the range of 80–130 m within the time window of the Hirnantian Isotopic Carbon Excursion. This massive regression coincides with maximum ice sheet extent inferred from sections in West Gondwana.